Generation of a “typical meteorological year” for Nicosia, Cyprus - Petrakis, Michael C.; Kambezidis, H. D.; Lykoudis, Spyros P.; Adamopoulos, Anastasios D.; Roditis, George; Kalogirou, Soteris A.; Michaelides, Ioannis; Petrakis, Michael C.; Kambezidis, H. D.; Lykoudis, Spyros P.; Adamopoulos, Anastasios D.; Roditis, George (My University, 1998)
The present study is concerned with the generation of a Typical Meterological Year for Nicosia, Cyprus. The above tool will be useful for the prediction and comparison of the performance and cost effectiveness of passive and active solar systems in the island. The Typical Meteorological Year was generated from available hourly meteorological data recorded during the period 1986–1992, using the Filkenstein-Schafer statistical method.
Keywords: Climatic conditions--Cyprus